Appraisal of anti-protozoan activity of nitroaromatic benzenesulfonamides inhibiting carbonic anhydrases from Trypanosoma cruzi and Leishmania donovani - Alessio Nocentini; Sameh M. Osman; Igor A. Rodrigues; Veronica S. Cardoso; Fatmah Ali S. Alasmary; Zeid AlOthman; Alane B. Vermelho; Paola Gratteri; Claudiu T. Supuran (Taylor & Francis Group, 2019)
Chagas disease and leishmaniasis are neglected tropical disorders caused by the protozoans Trypanosoma cruzi and Leishmania spp. Carbonic anhydrases (CAs, EC 4.2.1.1) from these protozoans (α-TcCA and β-LdcCA) have been validated as promising targets for chemotherapic interventions. Many anti-protozoan agents, such as nitroimidazoles, nifurtimox, and benznidazole possess a nitro aromatic group in their structure which is crucial for their activity. As a continuation of our previous work on N-nitrosulfonamides as anti-protozoan agents, we investigated benzenesulfonamides bearing a nitro aromatic moiety against TcCA and LdcCA, observing selective inhibitions over human off-target CAs. Selected derivatives were assessed in vitro in different developmental stages of T. cruzi and Leishmania spp. A lack of significant growth inhibition has been found, which has been connected to the low permeability of this class of derivatives through cell membranes. Further strategies necessarily need to be designed for targeting Chagas disease and leishmaniasis with nitro-containing CA inhibitors.